Maranta nanica (Marantaceae), a new dwarf species from Central Brazil - Fraga, Fernanda Ribeiro De Mello; Braga, João Marcelo Alvarenga (Phytotaxa, 2020)
A new species of Maranta (Marantaceae) from Central Brazil is described and illustrated. The species is recognizable due to its small rosulate habit, unbranched aerial shoot, hirtellous bracts with apex acute, sub-brachyblastic cymules, and each bracteole subtending a single flower.